Gambaran Berat Jenis Urin Dan Kadar Protein Urin Pada Ibu Hamil Di Upk Puskesmas Kampung Dalam Pontianak Timur - Musaidah, Siti; Nurhayati, Etiek; Slamet, Slamet; Salim, Maulidyah (poltekkes kemenkes pontianak, 2022)
Laboratory examinations are carried out to determine diseases that can affect pregnancy, one of the tests carried out is routine urine. The presence of the hormone HCG (Human Chorionic Gonadotrophin) in the urine can be used for a pregnancy test. Kidney function, can be known through a protein test in the urine, the presence of protein in the urine leads to pre-eclampsia in pregnant women. High urine specific gravity can be caused by lack of fluid consumption, the presence of sugar in the urine, and protein in the urine (usually in people with kidney disorders) or certain medications. This study aims to describe the description of urine specific gravity and urine protein levels in pregnant women in the UPK Puskesmas Kampung Dalam, Pontianak Timur. This is a descriptive survey research using the accidental sampling technique. Measurements and observations of research variables were measurements of urine specific gravity and urine protein content which were carried out at the UPK Laboratory of the Kampung Dalam Puskesmas, Pontianak Timur. The sample used is a urine sample when pregnant women who meet predetermined criteria, the examination is carried out using a Urine Analyzer. Respondents of this study found 30 people. The results of 30 respondents pregnant women measuring urine specific gravity whose normal limit is 1,005-1,030 obtained urine specific gravity of 1,010 as many as 6 respondents (20%), 1,015 as many as 9 respondents (30%), 1,020 as many as 2 respondents (6,7% ). 1,025 as many as 6 respondents (20%), and 1,030 as many as 7 respondents (23.3%). While the results of the measurement of urine protein levels were positive 1 as many as 4 respondents (13.3%), positive 2 as many as 1 respondent (3.4%), and Negative as many as 25 respondents with a percentage (83.3%).